Epidemiological Characteristics and Their Influencing Factors Among Pulmonary Tuberculosis Patients With and Without Diabetes Mellitus: A Survey Study From Drug Resistance Surveillance in East China - Wu, Qian; Wang, Min; Zhang, Yu; Wang, Wei; Ye, Teng-Fei; Liu, Kui; Chen, Song-Hua (Frontiers in Public Health, 2022)
Background: The burden of pulmonary tuberculosis (TB) and diabetes mellitus (DM) had become serious global concerns, while the comprehensive evaluations of DM status and drug resistance in TB patients were still lack. Methods: All details of TB cases were collected from drug resistance monitoring sentinels in Zhejiang Province. Fisher's exact test or Pearson chi square test (2) was used to compare the baseline characteristics among TB with different DM status. Logistic regression model was used to estimate the relationship between DM and different drug resistance spectrum. Univariate analysis and multivariate logistic model were used to explore the possible risk factors of drug resistance in TB patients accompany with DM. Results: 936 TB cases with smear positive in Zhejiang Province were collected, in which 76 patients (8.12%) owned the comorbidity of DM. The prevalence of TB-DM was higher in older, Han nationality, employed, accompanied by no health insurance and hepatitis B status. Among 860 cases of TB-no DM and 76 cases of TB-DM, drug resistance-TB accounted for 31.51% and 23.68% (P > 0.05), MR-TB accounted for 15.93% and 14.47% (P > 0.05), respectively. MDR-TB was 4.88% and 6.58% (P > 0.05). The incidence of poly-drug resistant tuberculosis (PDR-TB) in TB-no DM patients (10.70% vs 2.63%, OR: 4.43; 95% CI, 1.07–18.36) was higher than that in TB-DM group (P < 0.05). In univariate and multivariate analysis, none of the basic factors was found statistically significant with drug resistance among TB-DM cases (all P > 0.05). Conclusions: Our results showed that the drug resistance rate of TB-DM group was not higher than that of TB-no DM group. Patients with TB-no DM were at a higher risk for PDR-TB, but not for MDR-TB, MR-TB and drug resistance-TB. In the future, large scale and well-designed prospective studies are needed to clarify the impact of DM on the drug-resistance among TB.